Age and shock severity predict mortality in cardiac intensive care unit patients with and without heart failure. (10th September 2020) - Padkins, Mitchell; Breen, Thomas; Anavekar, Nandan; van Diepen, Sean; Henry, Timothy D.; Baran, David A.; Barsness, Gregory W.; Kashani, Kianoush; Holmes, David R.; Jentzer, Jacob C.
Abstract: Aims: Age is an important risk factor for mortality among patients with cardiogenic shock and heart failure (HF). We sought to assess the extent to which age modified the performance of the Society for Cardiovascular Angiography and Interventions (SCAI) shock stage for in‐hospital and 1 year mortality in cardiac intensive care unit (CICU) patients with and without HF. Methods and results: We retrospectively reviewed unique admissions to the Mayo Clinic CICU during 2007–2015 and stratified patients by age and SCAI shock stage. The association between age and in‐hospital mortality was analysed using multivariable logistic regression, and 1 year mortality was analysed using Cox proportional hazards analysis, both in the entire cohort and among patients with an admission diagnosis of HF or acute coronary syndrome (ACS). The final study population included 10 004 unique patients with a mean age of 67 ± 15 years, including 46.1% with HF and 43.1% with ACS. Older patients more frequently had HF and had more extensive co‐morbidities, higher illness severity, more organ failure, and differential use of critical care therapies. The percentage of patients with SCAI shock stages A, B, C, D, and E were 46%, 30%, 16%, 7%, and 1%, respectively. Patients with HF were older, had greater severity of illness and higher SCAI shock stage, and had higher rates of death at all time points. In‐hospital mortality occurred in 908 (9%) patients, including 549 (12%) patients with HF (61% of all hospital deaths). Age was independently associated with hospital mortality (adjusted odds ratio per 10 years 1.3, 95% confidence interval 1.2–1.4, P  < 0.001) and 1 year mortality (adjusted hazard ratio per 10 years 1.2, 95% confidence interval 1.2–1.3, P  < 0.001) in the overall cohort. The associations of age with both hospital mortality (adjusted odds ratio 1.6 vs. 1.3 per 10 years older) and 1 year mortality (adjusted hazard ratio 1.5 vs. 1.3 per 10 years older) were higher for patients with ACS compared with patients with HF. Older age was associated with higher adjusted hospital mortality and 1 year mortality in each SCAI shock stage (all P  < 0.05). Additive increases in both hospital mortality and 1 year mortality were observed with increasing age and SCAI shock stage. Conclusions: Age is an independent risk factor for mortality that modifies the relationship between the SCAI shock stage and mortality risk in CICU patients, providing robust risk stratification for in‐hospital and 1 year mortality. Although patients with HF had a higher risk of dying, age was more strongly associated with mortality among patients with ACS.